2008
DOI: 10.1097/wtf.0b013e328307ed33
|View full text |Cite
|
Sign up to set email alerts
|

Community based sociotherapy in Byumba, Rwanda

Abstract: A community based sociotherapy programme was implemented in the North of Rwanda in 2005.This article describes the background of sociotherapy, explains its principles and application in therapy for refugees in the Netherlands, and gives a justi¢cation for the introduction of the approach in a particular setting in post war and post genocide Rwanda. It then focuses on the development of the programme in this setting and addresses recruitment criteria for facilitators. It includes the qualities these facilitator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 2 publications
0
57
0
1
Order By: Relevance
“…While no evidence for direct prediction of PTSD symptom severity using economic factors was found, physical illness seems to function as a mediator between both, as its correlates with social as well as economic factors demonstrate. The direct consequences of genocidal violence such as HIV infection, chronic pain or disability, which were especially present in the group of survivors, have an immediate impact on the economic growth of a family in an already poor environment [50]. The respondents mainly worked as peasants, as is common for the rural Rwandan population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While no evidence for direct prediction of PTSD symptom severity using economic factors was found, physical illness seems to function as a mediator between both, as its correlates with social as well as economic factors demonstrate. The direct consequences of genocidal violence such as HIV infection, chronic pain or disability, which were especially present in the group of survivors, have an immediate impact on the economic growth of a family in an already poor environment [50]. The respondents mainly worked as peasants, as is common for the rural Rwandan population.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, while released prisoners rarely mentioned problems of reintegration following their release, their other family members such as their wives and children did. As Richters et al [50] demonstrated, sources for ongoing conflicts might be found within families in which the father is extensively absent due to imprisonment. In such circumstances, the man returning home from prison may find that his wife has brought another man home or has even had children with other men.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, addressing livelihood skills, interpersonal skills and mobilizing community resources are all essential elements of such empowering approaches. While also an extremely under-researched area, examples from India and Rwanda show positive effects of support groups on the symptoms of common mental disorders (Richters et al, 2008;Scholte et al, 2011;Tripathy et al, 2010). Interestingly, these successful interventions did not use any medical language, such as ' depression ' , ' post-traumatic stress disorder ' or other psychiatric jargon (Patel, 2014).…”
Section: Engaging Communities To Be Partners In Psychosocial Intervenmentioning
confidence: 93%
“…Mental health interventions used with refugees have been primarily trauma-focused, including narrative exposure therapy (NET) (Neuner, Schauer, Klaschik, Karunakara, & Elbert, 2004), group therapy (Tucker & Price, 2007), support groups (Ley, 2006), and individual therapy (Neuner et al, 2004). Other interventions include sociotherapy (Richters, Dekker, & Scholte, 2008), psychoeducation (Yeomans, Forman, Herbert, & Yuen, 2010), and community-based interventions (Weine et al, 2004). …”
Section: Theoretical Justification and Empirical Support For The Intementioning
confidence: 99%